High order Fano resonance in the time domain for a freezing water microdroplet; Scientific Reports; Vol. 14 - Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Song Zhou; Luk’yanchuk B. S. Boris Semenovich (2024, 2024)
Title screen